2014
DOI: 10.1007/s10973-014-3677-7
|View full text |Cite
|
Sign up to set email alerts
|

New sulfonic derivatives of quercetin as complexing reagents: synthesis, spectral, and thermal characterization

Abstract: The synthesis conditions of quercetin-8-sulfonic acid and sodium salt of sulfonated quercetin were determined. The molecular formulae of obtained compounds are: C 15 H 10 O 10 SÁ4H 2 O and C 15 H 9 O 10 SNaÁ4H 2 O. On the basis of spectral methods UV-Vis, IR, and 1 H NMR it was stated that the sulfonation of quercetin occurs at 8-C position of the A ring. The complexing properties of Na-QSA-8 were confirmed by synthesis of a solid complex with Fe(II) ions. The NaQSA-8 formed a complex with Fe(II) ions at pH 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
3
9
0
1
Order By: Relevance
“…Aromatic ring stretch bands for C=C were detected at 1610, 1561, and 1520 cm −1 . The signal for ν(C-O) can be found at 1462 cm −1 [37], other bands associated with the vibrations of C-O bonds appear also at 1132 cm −1 (C-OH stretching). The in-plane bending band of C-H in aromatic hydrocarbon was detectable at 1318 cm −1 , and out-of-plane bending bands were evident at 930, 822, 678, and 603 cm −1 .…”
Section: Ga and Qc Characterizationmentioning
confidence: 96%
“…Aromatic ring stretch bands for C=C were detected at 1610, 1561, and 1520 cm −1 . The signal for ν(C-O) can be found at 1462 cm −1 [37], other bands associated with the vibrations of C-O bonds appear also at 1132 cm −1 (C-OH stretching). The in-plane bending band of C-H in aromatic hydrocarbon was detectable at 1318 cm −1 , and out-of-plane bending bands were evident at 930, 822, 678, and 603 cm −1 .…”
Section: Ga and Qc Characterizationmentioning
confidence: 96%
“…According to the literature data, other metal complexes of quercetin showed similar thermal behavior. The thermogravimetric analysis of the sodium(I) salt and Fe(II) complex of sulfonic derivative of quercetin revealed that these compounds underwent one step dehydration in the temperature range 20-150°C for sodium salt (loss of four water molecules) and 20-160°C for the iron complex (loss of 12 molecules of water) [32]. The increase of temperature in the range of 150-560°C caused the decomposition of the anhydrous compounds.…”
Section: Thermogravimetric and Elemental Analysesmentioning
confidence: 99%
“…Low values of dehydration enthalpies indicate that the water molecules are weakly bonded to the ligand and probably participate in the formation of hydrogen bond with mefenamate ligand. Hence, the obtained lanthanide compounds contain only crystallization water molecules [49,50]. After dehydration step, the resulting anhydrous compounds are stable up to about 350°C.…”
Section: Thermal Analysismentioning
confidence: 99%